Successful treatment of pleural empyema and necrotizing pneumonia caused by methicillin-resistant Staphylococcus aureus infection following influenza A virus infection: A case report and literature review - Han, Chunjiao; Zhang, Tongqiang; Zhao, Yidi; Dong, Lili; Li, Xiaole; Zheng, Jiafeng; Guo, Wei; Xu, Yongsheng; Cai, Chunquan (Frontiers in Pediatrics, 2022)
With the rapid increase in the number of infections, children with Staphylococcus aureus (S. aureus) infection secondary to Influenza A virus (IAV), appear to have a great possibility of causing severe complications and illness. Despite some cases and research findings regarding the death of children with IAV and S. aureus, coinfection included, there were few details about successful treatment of pleural empyema and necrotizing pneumonia caused by methicillin-resistant Staphylococcus aureus (MRSA) infection following IAV. In this case report, we describe the clinical symptoms and treatment of a teenager with pleural empyema and necrotizing pneumonia related to S. aureus secondary infection who was initially infected by IAV. This case highlights the importance of early recognition and application of thoracoscopy for this potentially fatal pleural empyema caused by MRSA and IAV coinfection. We conclude that this is a significant case that contributes to raising awareness regarding rarely occurring severe respiratory infections by MRSA in a child with normal immune function after IAV. In addition, further studies are needed to explore risk factors for IAV coinfection with S. aureus.